Detection Study of Bipolar Depression Through the Application of a Model-Based Algorithm in Terms of Clinical Feature and Peripheral Biomarkers - Zheng, Yanqun; He, Shen; Zhang, Tianhong; Lin, Zhiguang; Shi, Shenxun; Fang, Yiru; Jiang, Kaida; Liu, Xiaohua (Frontiers in Psychiatry, 2019)
<Objectives>The nature of the diagnostic classification of mood disorder is a typical dichotomous data problem and the method of combining different dimensions of evidences to make judgments might be more statistically reliable. In this paper, we aimed to explore whether peripheral neurotrophic factors could be helpful for early detection of bipolar depression. <Methods>A screening method combing peripheral biomarkers and clinical characteristics was applied in 30 patients with major depressive disorder (MDD) and 23 patients with depressive episode of bipolar disorder. By model-based algorithm, some information was extracted from the dataset and used as a “model” to approach penalized regression model for stably differential diagnosis for bipolar depression. <Results>A simple and efficient model of approaching the diagnosis of individuals with depressive symptoms was established with a fitting degree 90.58% and an acceptable cross validation error rate. Neurotrophic factors of our interest were successfully screened out from the feature selection and optimized model performance as reliable predictive variables. <Conclusion> It seems to be feasible to combine different types of clinical characteristics with biomarkers in order to detect bipolarity of all depressive episodes. Neurotrophic factors of our interest presented its stable discriminant potentiality in unipolar and bipolar depression, deserving validation analysis in larger samples.